2013
DOI: 10.3892/mmr.2013.1799
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine protects against renal and hepatic dysfunction in septic rats via downregulation of Toll-like receptor 4

Abstract: The present study was designed to determine the renoprotective and hepatoprotective effect of lidocaine in septic rats through the Toll‑like receptor 4 (TLR4) signaling pathway. Adult male Sprague‑Dawley rats were randomly divided into the following three groups: control, sepsis model and 10% lidocaine. A model of sepsis was established by injection of lipopolysaccharide (LPS; 5 mg/kg) into the intraperitoneal cavity of rats. The same volume of saline was injected intraperitoneally into rats of the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
(41 reference statements)
0
19
0
Order By: Relevance
“…www.nature.com/aps Lee YJ et al Acta Pharmacologica Sinica npg inducing activity of lidocaine was not the focus of this study, other signaling pathway(s), including Akt [26] , NF-κB [27] , and the activation of both extrinsic and intrinsic apoptosis pathways [28] may also contribute to the lidocaine-induced chondrotoxicity. We cannot rule out whether lidocaine regulates these signaling pathways in the experimental conditions of this study; nevertheless, it can be postulated that lidocaine induces apoptosis by causing an increased ratio of Bax to Bcl-2.…”
Section: Wwwchinapharcom Lee Yj Et Almentioning
confidence: 99%
“…www.nature.com/aps Lee YJ et al Acta Pharmacologica Sinica npg inducing activity of lidocaine was not the focus of this study, other signaling pathway(s), including Akt [26] , NF-κB [27] , and the activation of both extrinsic and intrinsic apoptosis pathways [28] may also contribute to the lidocaine-induced chondrotoxicity. We cannot rule out whether lidocaine regulates these signaling pathways in the experimental conditions of this study; nevertheless, it can be postulated that lidocaine induces apoptosis by causing an increased ratio of Bax to Bcl-2.…”
Section: Wwwchinapharcom Lee Yj Et Almentioning
confidence: 99%
“…18 In a separate study, Liu J et al have shows that systemic lidocaine therapy protects dysfunction of kidney and liver in septic mice model with inhibiting expression of TLR4, NF-κβ and interleukin-6. 19 While the expression of HMGB1 mRNA and TLR4 protein levels in the control group increased steadily when compared from before the injury, 4 h after injury, and 2 h after administration of distilled water, p < 0.00. The results of this study show that administration of distilled water does not provide a therapeutic efficacy to inhibit inflammatory process.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, Wang and colleagues showed that lidocaine was protective against sepsis in rats and is linked to inhibition of serum high-mobility-group box 1 (HMGB1) expression and NF-B in liver, kidneys, lungs, and ileum (47). Liu and colleagues also showed that lidocaine protected against renal and hepatic dysfunction in septic rats from the downregulation of Toll-like receptor 4 (48). It is noteworthy that in all of our previous work, from myocardial ischemia to hemorrhagic shock, the ALM combination is key for whole-body protection, as the individual adenosine or lidocaine groups provided suboptimal outcomes (16).…”
Section: Figmentioning
confidence: 99%